Analisis Penggunaan Serat Tali Pancing Polyethylene (PE) Ditinjau Dari Kekuatan Impact - Arif Satia Prianto, Yudistira; Sugiyarto, Sugiyarto; Fitri Arriyani, Yang (Jurnal Inovasi Teknologi Terapan, 2024)
Helm serves as a crucial safety equipment for two-wheeler riders, aiming to mitigate impact during accidents by adhering to the Indonesian National Standard (SNI) 1811-2007. With the advancement of time, the utilization and exploitation of materials such as wood, stone, metal, and various others are rapidly progressing. However, this technological advancement has led to a decline in the availability of metal raw materials, thus one of the solutions to overcome this issue is by utilizing composite materials. This is due to their superior qualities including strength, corrosion resistance, lightweight, and cost-effectiveness. This research employs braided PE strings with considerations of brand, volume fraction, and orientation arrangement. The analysis method utilized in this study is the Taguchi method, aimed at identifying the most influential factors in impact testing. From the impact testing results, the highest impact test value is found in Brand A, with a volume fraction of 4%, and a transverse fiber orientation, averaging at 0.120542 J/mm2. The lowest impact test value is observed in Brand B, with a volume fraction of 2%, and a transverse fiber orientation, averaging at 0.005833 J/mm2. Based on the highest average impact strength specimen values, specimens pass the Indonesian National Standard (SNI) test, with a minimum impact strength value of 0.00972 J/mm².